Innovation of Avocado Leaf-Based Jelly Candy with the Addition of Beef Gelatin. - Rahmawan Wira Ghani, Sulung (ALKIMIA, 2023)
This study aims to develop avocado (Persea americana Mill) leaf-based jelly candy with the addition of bovine gelatin, in response to the increasing demand for herbal food and beverage products in Indonesia. Product quality testing was conducted to determine moisture content, pH, texture, and organoleptic analysis. The results showed that all jelly candy formulas met the set standards for moisture content, with a pH that was classified as acidic and ranged from 3.35 to 4.56. The texture of the jelly increased with increasing gelatin concentration, and formula 5 obtained the highest score in the organoleptic test, indicating panelists' preference for color, aroma, taste, and texture. The conclusion of this study is that the formulation of bovine gelatin addition has a significant effect on the quality of jelly candy, with formula 5 being the most preferred.